Ivana BrlićMažuranić and Her Brlićevac - Gostomska, Anita (Poznańskie Studia Slawistyczne, 2022)
The article, based on the commemorative books of the Brlićevac summer house and the correspondence of the Croatian writer Ivana Brlić-Mažuranić, attempts to show the influence that the family estate had on Brlić-Mažuranić and her work. Atthe estate in the immediate vicinityof Brod, where the spouses lived, the family spent the summer months for many consecutive years and Ivana Brlić-Mažuranić wrote most of her works. The close contact with nature, which this place provided to a nature-loving writer, became the dominant source of her inspiration, it also guaranteed great well-being, unattainable in other places she lived ( Brod, Zagreb ). The property played a huge role in the life of the famous Croatian who, in her time free from the work in the vineyard, willingly devoted herself to recreation typical of a summer resort, and each celebration of the moments spent together with the loved ones, led to a kind of sacralization of this space.